Optimization of Investment Planning Based on Game-Theoretic Approach - Butsenko, Elena Vladimirovna (Economy of Regions, 2018)
The game-theoretic approach has a vast potential in solving economic problems. On the other hand, the theory of games itself can be enriched by the studies of real problems of decision-making. Hence, this study is aimed at developing and testing the game-theoretic technique to optimize the management of investment planning. This technique enables to forecast the results and manage the processes of investment planning. Пє proposed method of optimizing the management of investment planning allows to choose the best development strategy of an enterprise. This technique uses the “game with nature” model, and the Wald criterion, the maximum criterion and the Hurwitz criterion as criteria. We article presents a new algorithm for constructing the proposed econometric method to optimize investment project management. Wis algorithm combines the methods of matrix games. Furthermore, I show the implementation of this technique in a block diagram. We algorithm includes the formation of initial data, the elements of the payment matrix, as well as the definition of maximin, maximal, compromise and optimal management strategies. We methodology is tested on the example of the passenger transportation enterprise of the Sverdlovsk Railway in Ekaterinburg. We application of the proposed methodology and the corresponding algorithm allowed to obtain an optimal price strategy for transporting passengers for one direction of traffic. Wis price strategy contributes to an increase in the company’s income with minimal risk from the launch of this direction. We obtained results and conclusions show the effectiveness of using the developed methodology for optimizing the management of investment processes in the enterprise. We results of the research can be used as a basis for the development of an appropriate tool and applied by any economic entity in its investment activities.